The Association of Neutrophil Lymphocyte Ratio and Glycemic Markers in Hemodialysis Patients - Mustafa Topal (Genel Tıp Dergisi)
Background/aims: Neutrophil lymphocyte ratio was found to be as an inflammation marker in the preceding decade and recently related with glycemic indices in patients with diabetes mellitus. The target of this research was to explore the association of neutrophil lymphocyte ratio and glycemic indices in hemodialysis population. Methods: 177 hemodialysis patients (98 diabetic and 79 non-diabetic) aged 56.08±16.06 years were enrolled in this research. Neutrophil lymphocyte ratio was calculated and its association with predialysis glucose and HbA1c was studied. Results: NLR was positively correlated with predialysis glucose (p=0.000, r=0.338), body mass index (p=0.029, r=0.220), white blood cell (p=0.000, r=0.430), platelet (p=0.034, r=0.159), neutrophil (p=0.000, r=0.656) and C-reactive protein (p=0.00, r=0.377) levels. In non-diabetic hemodialysis group, predialysis glucose was still correlated with neutrophil lymphocyte ratio (p=0.047, r=0.224). Diabetics had higher predialysis glucose (185.94±81.11 vs 111.24±25.59, p=0.000) and neutrophil lymphocyte ratio (4.99±4.17 vs 2.82±1.23, p=0.000) compared to non-diabetics. Conclusion: This study revealed that predialysis glucose levels in hemodialysis patients are correlated with neutrophil lymphocyte ratio and hemodialysis patients with diabetes have higher neutrophil lymphocyte ratio levels. Neutrophil lymphocyte ratio should be recognized as a glycemic control marker along with traditional glycemic indices in HD patients.